Associations of ALT, AST and ALT/AST ratio with metabolically unhealthy obesity in the elderly - Shao, Yuhan; Zhu, Hailong; Chen, Xin; Feng, Enqiang; Chen, Chen; Shao, Zhugang; Li, Xiaojing; Liu, Li (Frontiers in Nutrition, 2025)
AimsThis study aimed to clarify the effects of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and ALT/AST ratio on metabolically unhealthy obese (MUHO) and to estimate the predictors of MUHO in the elderly.Methods19,812 individuals aged 65 years and older from a health check-up in Qingdao, China in 2021 were chosen as subjects in the current study. Binary logistic regression models were performed to evaluate the relationship between ALT, AST, ALT/AST ratio and MUHO. Receiver operating characteristic (ROC) analysis was performed to estimate the predictive value of ALT, AST and ALT/AST ratio for the diagnosis of MUHO.ResultsThe risks for MUHO increased across quartiles of ALT level and ALT/AST ratio in both genders. The adjusted odds ratios (ORs) for MUHO in the highest quartile of ALT were 3.20-fold higher than the reference quartile in men and 3.05-fold higher in women. Compared with the first quartile of ALT/AST ratio, the adjusted ORs for MUHO in the highest quartile were 3.64 (95% CI: 3.17–4.19) in men and 3.60 (95% CI: 3.11–4.16) in women, respectively. In ROC curve analysis for predicting MUHO, the area under the ROC curve (AUC) values were 0.63 (p < 0.001) for ALT and 0.64 (p < 0.001) for ALT/AST ratio in men, and 0.62 (p < 0.001) for ALT and 0.64 (p < 0.001) for ALT/AST ratio in women. However, AST was not significantly associated with MUHO both in men and in women (p>0.05).ConclusionALT and ALT/AST ratio might be considered as two simple and reliable diagnostic indicators for MUHO in the elderly.